2021
DOI: 10.1186/s43591-021-00006-y
|View full text |Cite
|
Sign up to set email alerts
|

Development of screening criteria for microplastic particles in air and atmospheric deposition: critical review and applicability towards assessing human exposure

Abstract: Over the last several years there has been an increase in studies reporting the presence of microplastic particles (MPs) in both indoor and outdoor air. Data reported reflect a variety of different types of air samples, which have helped to demonstrate the ubiquity of MPs in the atmosphere and their potential contribution to atmospheric particulate matter (PM). The relative quality of the data reporting on MPs in air has not been evaluated, but represents an important step towards improving our overall underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 61 publications
1
25
0
1
Order By: Relevance
“…Still, consistency for recovery rates routine amongst studies would allow to compare and evaluate the quality of work. That would raise the concern that recovery rate results are not always reported [10 , 18 , 26 , 31] or they represent just part of the samples treatment protocol [12] .…”
Section: Methods Detailsmentioning
confidence: 99%
“…Still, consistency for recovery rates routine amongst studies would allow to compare and evaluate the quality of work. That would raise the concern that recovery rate results are not always reported [10 , 18 , 26 , 31] or they represent just part of the samples treatment protocol [12] .…”
Section: Methods Detailsmentioning
confidence: 99%
“…Pauly et al [34] found fibers in 99 of 114 malignant lung specimens. On the other hand, a recent study indicated that MP deposition is more likely to occur in the upper airway tract (i.e., nose, mouth, and throat) when inhaled and would reach the gut if ingested [7,25] . Fine MPs are believed to translocate to the circulatory system and other organs [33,39] .…”
Section: Health Implications Of Microplasticsmentioning
confidence: 99%
“…There are 48 studies (as of November 2021) reporting MPs in dust, aerosols, wet and dry atmospheric deposition, snow, etc. [11,[15][16][17][18][19][20][21][22][23][24][25][26] . MPs in the air are released from wear and tear of clothing material [27][28][29] , by washing and drying [30] , erosion of synthetic rubber tires, deterioration of house furniture, emissions from the synthetic textile industry, emissions from vinyl chloride and polyvinyl chloride (PVC) industries, and contamination from city dust [18][19][20][21] [Figure 1].…”
Section: Introductionmentioning
confidence: 99%
“…Chemical uptake then is modelled dynamically as a function of exchange rate constants, concentration gradients and gut retention time [102]. Like for analytical and effect studies [95], strict QA/QC criteria would apply to such 'vector effect' modelling studies, criteria which have been published recently [222].…”
Section: Pbpk Biodistribution Modellingmentioning
confidence: 99%